A fővárosi önkormányzat új szervezetének kialakulása - Walter, Tibor (Debreceni Jogi Műhely, 2007)
After demonstarting a short historical and national angle in my study, I would like to sketch a general survey about the rising and the operation of the capital local government between 1989 and 1994. This period was the beginning of establishing the system of local governments. This period resulted a remarkable turn to the direction of the capital level. Now this subject belongs to the history of public administration, but it is still a current question from many points of view. It is true that the relationship between the capital and the district local governments is rather contradictionary, as this is true for the relationship of the regime and the government. The development of the capital local government can be approached only if we examine the whole local government system. The governmental system and its contemporaries made influence to the operation of the capital local government too, especially in two fields, on the one hand the specific structure of the capital local governmental system, on the other hand the disintegrated structure of the capital agglomeration. The special structure of the capital local government influenced significantly the relationship of the local governments and the capital, and the relationship of the capital and the regime. The sharing of the tasks and the financial sources were a source of tensions between the capital and the districts. There was a great need to use long-term principles in sharing these sources. The conflicts became deeper and deeper, because the competencies were not clearly divided, and some investments failed because of the resistance of the district local governments. The relationship of the regime and the capital determines the special position of the capital, and the strong dependence on the state supports. This situation can be worse by the conflicts in the political principles of the capital local governments and the regime.